United Kingdom evidence on the behaviour of the beta or systematic risk of initial public offerings - Qian, Yi (2012)
This study examines the beta or systematic risk of initial public offerings using a sample of newly issued stocks in the United Kingdom market. The findings are threefold. First, the beta risk estimation is found to decline over time. It corresponds with the differential information model which predicts that the risk of low information is high with uncertainty around it and will decline as the quantity of information increases. The quantity of information, in this case, is represented by time. Secondly, in the presence of decline of beta risk, this paper studies whether the differential information risk is uniform. Investors might be able to mitigate the risk by inferring the missing information from high information counterparties for the low information firms. Therefore, it asserts that the more the counterparty firm, the lower the information risk. IPO firms from traditional industries with sufficient number of high information firms might have lower beta risk and a lower rate of decline of beta than those of emerging industries which the firms are unique so fewer counterparties are available. Thirdly, this paper investigates whether the decline of beta risk of IPO firms is caused by delisting of high beta risk IPO stocks as the delisting hypothesis predicts. The findings of this paper contradict the expectation of delisting hypothesis that implies high beta risk might not the driver of IPO being delisted. In addition, this paper utilizes a robust method of estimating the beta risk of IPOs and produce different result from the traditional OLS estimators which are subject to criticism.